You mean -6x^2 -3 -7x?

If it is the case, then I must tell you that your question doesn't have any solution. The polynomial doesn't have any real zeros. The zeros are imaginary.

Log in to add a comment

You mean -6x^2 -3 -7x?

Log in to add a comment

6x²-3-7x = 0

6x²-7x-3 = 0

6x²-9x+2x-3 = 0

3x(2x-3)+1(2x-3)

(3x+1)(2x-3)

x = -1/3 and x = 3/2

6x²-7x-3 = 0

6x²-9x+2x-3 = 0

3x(2x-3)+1(2x-3)

(3x+1)(2x-3)

x = -1/3 and x = 3/2

The equation is:

6x² - 7x - 3

=6x² - 9x + 2x - 3

=3x(2x - 3) + 1(2x - 3)

=(2x - 3)(3x + 1)